2018
DOI: 10.1038/s41598-018-34199-9
|View full text |Cite
|
Sign up to set email alerts
|

The c-Jun and JunB transcription factors facilitate the transit of classical Hodgkin lymphoma tumour cells through G1

Abstract: Classical Hodgkin Lymphoma (cHL) is primarily a B cell lymphoid neoplasm and a member of the CD30–positive lymphomas. cHL and the other CD30–positive lymphomas are characterized by the elevated expression and/or constitutive activation of the activator protein-1 (AP-1) family transcription factors, c-Jun and JunB; however, the specific roles they play in the pathobiology of cHL are unclear. In this report we show that reducing either c-Jun or JunB expression with short-hairpin RNAs (shRNAs) reduced the growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…37,38 Deregulation of AP-1 activity is implicated in the tumorigenesis of both solid tumors and lymphomas. 39,40 Importantly, the proto-oncogene c-Fos is the human homolog of the retroviral oncogene v-fos, which is linked to cancer due to the in vitro neoplastic transformation of normal cells. Overexpression of c-Fos promotes proliferation, angiogenesis, and survival of cancer cells.…”
Section: Dovepressmentioning
confidence: 99%
“…37,38 Deregulation of AP-1 activity is implicated in the tumorigenesis of both solid tumors and lymphomas. 39,40 Importantly, the proto-oncogene c-Fos is the human homolog of the retroviral oncogene v-fos, which is linked to cancer due to the in vitro neoplastic transformation of normal cells. Overexpression of c-Fos promotes proliferation, angiogenesis, and survival of cancer cells.…”
Section: Dovepressmentioning
confidence: 99%
“…A role for specific AP-1 proteins in the regulation of proliferation has been revealed by short interfering RNA (siRNA)/short hairpin RNA (shRNA) knock-down and clustered regularly interspaced short palindromic repeats (CRISPR)/Cas9 knock-out studies. Several groups have reported that JunB knock-down, in most ALK+ ALCL cell lines, decreased proliferation [ 89 91 ]. The common cell cycle defect observed in these studies was an increased percentage of cells in G 0 /G 1 with decreased percentages of cells in G 2 /M [ 89 ] or S [ 90 , 91 ] phase.…”
Section: The Function Of Ap-1 Proteins In Alk+ Alcl and Chlmentioning
confidence: 99%
“…Several groups have reported that JunB knock-down, in most ALK+ ALCL cell lines, decreased proliferation [ 89 91 ]. The common cell cycle defect observed in these studies was an increased percentage of cells in G 0 /G 1 with decreased percentages of cells in G 2 /M [ 89 ] or S [ 90 , 91 ] phase. These defects correlated with decreased expression of CDK2 and multiple cyclins including Cyclin A2, Cyclin D2, Cyclin D3, and Cyclin E, as well as increased expression of CDK inhibitors p14 ink4A , p18 ink4 , p21 cip1 and p27 kip1 [ 90 , 91 ].…”
Section: The Function Of Ap-1 Proteins In Alk+ Alcl and Chlmentioning
confidence: 99%
See 2 more Smart Citations